2004
DOI: 10.1016/s0308-8146(03)00217-6
|View full text |Cite
|
Sign up to set email alerts
|

Varietal and processing effects on the volatile profile of Australian olive oils

Abstract: The volatile profile of virgin olive oils was established using SPME and gas chromatography(-mass spectrometry). The major volatile in approximately 50% of the oils was E-hex-2-enal in contrast with European oils. The minor contribution of C5 compounds to the volatile profiles also contrasted with data on European oils. Hierarchical Cluster Analysis (HCA) implicates variety as the single-most important factor in determining volatile profile whilst malaxation time and temperature exerted a minor secondary effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 24 publications
(32 reference statements)
4
52
0
Order By: Relevance
“…A similar trend for hexanal with malaxation time was confirmed by Di Giovacchino, Costantini (11), who reported that the hexanal content of oils increases with a longer malaxation time (90 min). Additionally, Tura, Prenzler (26)in reported results that were consistent with the current one, where hexanal content was reported to increase when malaxation time was changed from 15 to 60 min.…”
Section: Effects Of Process Conditions On Transition Of Target Aroma supporting
confidence: 90%
See 1 more Smart Citation
“…A similar trend for hexanal with malaxation time was confirmed by Di Giovacchino, Costantini (11), who reported that the hexanal content of oils increases with a longer malaxation time (90 min). Additionally, Tura, Prenzler (26)in reported results that were consistent with the current one, where hexanal content was reported to increase when malaxation time was changed from 15 to 60 min.…”
Section: Effects Of Process Conditions On Transition Of Target Aroma supporting
confidence: 90%
“…Moreover, at the highest studied level of temperature, longer malaxation produced an olive oil with higher hexanal content (Fig 3). The decrease in concentration of hexanal with increasing temperature up to 30-40°C is consistent with the results of Tura, Prenzler (26)in which they investigated the effects of malaxation temperature at two levels (25 and 35°C) on transition of hexanal and result indicated the adverse effect on hexanal content in oil sample. A similar behavior was observed by Angerosa, Mostallino (25), who reported that malaxation conditions, especially time, act as a key role in the hexanal content of final olive oil.…”
Section: Effects Of Process Conditions On Transition Of Target Aroma supporting
confidence: 89%
“…High malaxation temperature (> 25 ºC) reduces the activity of enzymes, involved in LOP pathway, reducing the formation of C 6 saturated and unsaturated aldehydes. A similar result is described by Tura et al (2004). These authors found that changes in malaxation time and temperature produces differences in the volatile profile of olive oils.…”
Section: Technogical Factorssupporting
confidence: 80%
“…A study on volatile profile of Australian virgin olive oils has shown cultivar as the single-most important factor in determining aromatic oil quality (Tura et al, 2004). Other works confirmed the cultivar strong effect on aromatic quality.…”
Section: Introductionmentioning
confidence: 99%